Dimeric benzoboroxoles for targeted activity against Mycobacterium tuberculosis. Issue 43 (29th October 2019) - Guy, Collette S.; Murray, Kathryn; Gibson, Matthew I.; Fullam, Elizabeth
Abstract : Dimeric benzoboroxoles that are covalently linked by a short scaffold enhance selective anti-tubercular activity. Abstract : Dimeric benzoboroxoles that are covalently linked by a short scaffold enhance selective anti-tubercular activity. These multimeric benzoboroxole compounds are capable of engaging the specific extracellular Mycobacterium tuberculosis glycans, do not lead to the evolution of resistance and bypass the need to cross the impermeable mycobacterial cell envelope barrier.